Echoes of Desire English Petrarchism and Its Counterdiscourses - Dubrow, Heather (Cornell University Press, 1995)
Echoes of Desire variously invokes and interrogates a number of historicist and feminist premises about Tudor and Stuart literature by examining the connections between the anti-Petrarchan tradition and mainstream Petrarchan poetry. It also addresses some of the broader implications of contemporary critical methodologies. Heather Dubrow offers an alternative to the two predominant models used in previous treatments of Petrarchism: the all-powerful poet and silenced mistress on the one hand and the poet as subservient patron on the other.